Extension of the genocchi polynomials and its q-analogue - Luo, Qiu-Ming; Zhou, Yun (Utilitas Mathematica, 2011)
In this paper, we generalize the Genocchi polynomials and investigate its q-analogue. Some interesting results and relationships are obtained.